2013
DOI: 10.1074/jbc.m113.452953
|View full text |Cite
|
Sign up to set email alerts
|

Human Cytochrome P450 1A1 Structure and Utility in Understanding Drug and Xenobiotic Metabolism

Abstract: Background: Human cytochrome P450 1A1 (CYP1A1) activates procarcinogens, but the basis of their binding is unknown. Results: A 2.6 Å structure with the inhibitor ␣-naphthoflavone and docking simulations suggest key active site features. Conclusion: CYP1A1 has a planar active site that restricts ligand orientations.Significance: This provides a useful framework for understanding CYP1A1 interactions with a variety of substrates and inhibitors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
243
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 245 publications
(254 citation statements)
references
References 61 publications
10
243
0
1
Order By: Relevance
“…Of these six P450s, 1A2 exhibits the smallest and narrowest active site (Sansen et al, 2007). This architecture is conserved in structures of P450s 1A1 (Walsh et al, 2013) and 1B1 (Wang et al, 2011), and the narrow hydrophobic cavity is consistent with the roles of these enzymes in metabolism of polycyclic aromatic hydrocarbons. This narrow cavity is reinforced by the passage of helix F below helix G, and this redirection of the F helix is associated with a distortion of the F helix as it passes over the active site cavity (Fig.…”
Section: Introductionmentioning
confidence: 65%
“…Of these six P450s, 1A2 exhibits the smallest and narrowest active site (Sansen et al, 2007). This architecture is conserved in structures of P450s 1A1 (Walsh et al, 2013) and 1B1 (Wang et al, 2011), and the narrow hydrophobic cavity is consistent with the roles of these enzymes in metabolism of polycyclic aromatic hydrocarbons. This narrow cavity is reinforced by the passage of helix F below helix G, and this redirection of the F helix is associated with a distortion of the F helix as it passes over the active site cavity (Fig.…”
Section: Introductionmentioning
confidence: 65%
“…The resulting trajectory was analyzed to find the best substrate orientation, and the enzymesubstrate complex was minimized for another 1000 steps, as described earlier. This optimal substrate orientation was used as a starting point for automated docking with the Affinity module of Insight II using default parameters, as described earlier (Ericksen and Szklarz, 2005;Tu et al, 2008;Huang and Szklarz, 2010;Walsh et al, 2013). Residues within 10 Å from the initial substrate position comprised the flexible region of the protein during all docking runs.…”
Section: Structural Computational and Functional Analysis Of Cyp2b3mentioning
confidence: 99%
“…Shimada et al also reported that the oxidative metabolites formations of acenaphthene and acenaphthylene with P450 1B1 were more rapid than those with 1A2 (Shimada et al, 2015). The active site of the P450 1A1 enzyme has been reported to share a closer similarity to that of P450 1B1 than that of 1A2 (Walsh et al, 2013). It has also been reported that P450 1B1 is able to catalyze the activation of both polycyclic aromatic hydrocarbons and aryl amines (Shimada et al, 1996).…”
Section: Metabolism Of Clpyr By P450 Enzymesmentioning
confidence: 87%
“…This result is consistent with differences in the structures of the P450 1A1, 1A2, and 1B1 enzymes in regions associated with substrate access/egress, and regio-and stereo-selective substrate binding. The structure of the P450 1A1 enzyme was reported to prefer polycyclic aromatic hydrocarbons and other planar molecules, while 1A2 displayed a preference for aromatic amines and heterocyclic compounds (Zanger and Schwab, 2013;Walsh et al, 2013). Therefore, the planar structure of ClPyr may better fit the P450 1A1 active site.…”
Section: Metabolism Of Clpyr By P450 Enzymesmentioning
confidence: 99%